Allograft for Myeloma: Examining Pieces of the Jigsaw Puzzle - Malek, Ehsan; El-Jurdi, Najla; Kröger, Nicolaus; de Lima, Marcos (Frontiers in Oncology, 2017)
Multiple Myeloma (MM) cure remains elusive despite the availability of newer anti-myeloma agents. Patients with high-risk disease often suffer from early relapse and short survival. Allogeneic hematopoietic cell transplantation (allo-HCT) is an “immune-based” therapy that has the potential to offer long-term remission in a subgroup of patients, at the expense of high rates of transplant related morbidity and mortality. Donor lymphocyte infusion (DLI) upon disease relapse after allo-HCT is able to generate an anti-myeloma response suggestive of a graft-vs-myeloma effect. Allo-HCT provides a robust platform for additional immune-based therapy upon relapse including DLI and, maintenance with immunomodulatory drugs and immunosuppressive therapy. There have been conflicting findings from randomized prospective trials questioning the role of allo-HCT. However, to this date, allo-HCT remains the only potential curable treatment for MM and its therapeutic role needs to be better defined especially for patients with high-risk disease. This review examines different aspects of this treatment and summarizes ongoing attempts at improving its therapeutic index.